Практики застосування новітніх інструментів маркетингу гравцями фешен-індустрії в кризових умовах - Буднікевич, Ірина Михайлівна; Бастраков, Данііл Анатолійович; Budnikevich, Iryna; Bastrakov, Daniil; Подільчук, Олександр Сергійович; Podylchuk, Oleksandr (Науковий вісник Чернівецького університету. Серія Економіка, 2021)
Розглянені напрямки зміни фешен-індустрії під впливом пандемії, Акцентовану увагу на втратах «люксового» сегменту фешен-ринку, брендів і ритейлерів мідл-сегменту, на негативних купівельних настроях, на взаємозв’язку туризму та індустрії моди. Обґрунтовано необхідність застосування інновації в антикризових програмах гравців фешен-ринку. Узагальнено практику застосування новітніх інструментів маркетингу гравцями фешен-індустрії в кризових умовах. На основі аналізу експертних суджень та аналітичних оглядів ринку виділені найважливіші тренди, які визначають напрямки розробки та застосування нових інструментів маркетингу у фешен-індустрії. lining revenues of the global fashion industry, bankruptcy and problems for fashion market players, reducing the value of exclusive items through discounts and sales, the need for new marketing tools to attract and personalize new consumer habits. and social trends, consumer "maturity" of new generations of consumers, collaboration between competing brands and retailers, active digitalization of fashion business. Attention is focused on the losses of the "luxury" segment of the fashion market, brands and retailers of the middle segment, on negative consumer sentiment, on the relationship between tourism and the fashion industry. The necessity of application of innovation in anti-crisis programs of fashion market players is substantiated. It is noted that marketing offers tools that are aimed at retaining existing and attracting new customers to the brand, as well as provide an opportunity to maintain communication and build long-term partnerships with consumers. The practice of application of the newest marketing tools by players of the fashion industry in crisis conditions is generalized. The marketing activities of corporations that own luxury brands (Armani Group, LVMH, Guess, Capri Holdings), which are implemented in the framework of socio-ethical marketing and social responsibility, are considered. It is noted that today the participants of the fashion market focus on creative and innovative ways of online interaction and communication with consumers. It is concluded that the fashion market and fashion marketing have a high level of innovation, marketing offers market participants, a wide arsenal of promising innovative technologies and tools that can be effectively used in the fashion industry to mitigate the impact of the crisis. Basing on the analysis of expert judgments and analytical reviews of the market, the most important trends are identified, which determine the directions of development and application of new marketing tools in the fashion industry
PRACTICES OF APPLICATION OF THE LATEST MARKETING TOOLS BY FASHION INDUSTRY PLAYERS IN CRISIS
Keywords: маркетинг моди; фешен-маркетинг; інновації в маркетингу; інновації; соціально-відповідальний маркетинг; маркетингові дослідження; fashion marketing; marketing innovations; innovations marketing; marketing researches; socially responsible marketing